2019
DOI: 10.1111/sms.13510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 24‐week strength training on unstable surfaces on mobility, balance, and concern about falling in older adults

Abstract: Objective: To evaluate the effects of 24 weeks of strength training on stable (ST) and unstable surfaces (UST) on the functional mobility, balance, and concern about falling in healthy older adults, younger than 70. Design: A single-center randomized clinical trial.Participants: Sixty-four older adults (58 females and 6 males; 68 years) were randomized into control, ST, or UST groups. Interventions: Both ST and UST intervention groups received a core muscle, upper, and lower limb moderate-intensity strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
1
13
0
3
Order By: Relevance
“…Regular exercise influenced total daily physical activity and possibly induced chronic physiological adaptations. We observed that all studies that combined strength training programs with balance exercises reduced the risk of falling [4,[16][17][18][19]21,22,24,26,29]. The same was seen in isolated strength training programs [15,20,24,25,27,30,33].…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Regular exercise influenced total daily physical activity and possibly induced chronic physiological adaptations. We observed that all studies that combined strength training programs with balance exercises reduced the risk of falling [4,[16][17][18][19]21,22,24,26,29]. The same was seen in isolated strength training programs [15,20,24,25,27,30,33].…”
Section: Discussionsupporting
confidence: 55%
“…The analyzed studies were published between 2008 and 2019, including a total of 2229 people. The studies were conducted in Australia [15], Brazil [4,10,[16][17][18], Canada [19], China [20], Finland [21], Germany [22], Hungary [23], India [24], Iran [25], Japan [11], Portugal [7,26], Republic of Korea [27], Spain [12,28], Switzerland [29], and the United States [9,[30][31][32][33]. Eight studies were identified as using a combination of balance and strength exercises [4,16,17,19,21,22,24,29]; three studies using a combination of aerobic exercises, balance, and strength [7,9,28]; six studies using strength exercises [15,20,25,27,30,33]; one study using a combination of aerobic and strength exercises [10];…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations